PERBANDINGAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE YANG DIPADU PETA KONSEP DAN TANPA PETA KONSEP DI KELAS XI IPA SMA NEGERI 5 MAKASSAR (Studi Pada Konsep Sistem Pernapasan) - Wiwik Wiji Astuti (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This type of research is a quasi experiment (quasi experiment) with Pretest-Posttest Control Group Design design. This study aims to determine (1) students' learning motivation on the material of the respiratory system through the application of cooperative learning model of TPS without concept map, (2) student learning motivation on the material of the respiratory system through the application of cooperative learning model of TPS combined with concept map, (3) Student learning outcomes on the material of the respiratory system through the application of cooperative learning model of TPS without concept map, (4) student learning outcomes on the material of the respiratory system through the application of cooperative learning model of TPS combined concept map, (5) whether or not there is difference of students' Material of respiratory system through application of cooperative learning model of TPS combined with concept map and without concept map, and (6) whether or not there is difference of student learning result on the material of respiratory system through application of cooperative learning model of TPS combined with concept map and without concept map. The research population is all students of class XI IPA SMA Negeri 5 Makassar even semester of academic year 2013 - 2014 which consists of eight classes with total students as much as 256 students. The sample of the research is the students of class XI IPA1 and XI IPA2 which amounted to 69 people. Sampling technique is done by random class technique (random class). The data were obtained through two instruments: questionnaire of learning motivation and learning result test. The results showed that (1) the students' biology learning motivation in the control class experienced an increase in average score of 4.60; (2) students' biology learning motivation in experiment class increased by 4.38; (3) students' biology learning outcomes in the control class experienced an increase of 44.71; (4) students' biology learning outcomes in the experimental class increased by 58.72; (5) application of cooperative learning model of TPS type combined concept map significantly influence student's learning motivation; (6) the application of cooperative learning model of TPS type combined concept map has significant effect on student biology learning outcomes.